2008
DOI: 10.1111/j.1610-0387.2007.06602.x
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the use of rituximab (anti‐CD20 antibody) in the treatment of autoimmune bullous skin diseases§

Abstract: SummaryAutoimmune bullous skin disorders are induced by autoantibodies against distinct adhesion complexes of the epidermal and dermal-epidermal junction. Since most of these disorders are characterized by a severe, potentially lethal course, they require long-term immunosuppressive treatment to reduce the de novo synthesis of pathogenic autoantibodies by B lymphocytes. Rituximab, a chimeric monoclonal antibody against CD20 on B lymphocytes, has shown promise in several case reports or cohort studies in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 24 publications
(28 reference statements)
2
115
0
19
Order By: Relevance
“…[22][23][24][25] • A course of intravenous rituximab 2 9 1000 mg (2 weeks apart or 4 9 375 m2/1 week apart). The need for immunosuppressive adjuvants in rituximab therapy remains unclear…”
Section: Immunoadsorptionmentioning
confidence: 99%
“…[22][23][24][25] • A course of intravenous rituximab 2 9 1000 mg (2 weeks apart or 4 9 375 m2/1 week apart). The need for immunosuppressive adjuvants in rituximab therapy remains unclear…”
Section: Immunoadsorptionmentioning
confidence: 99%
“…Rituximab can curb the disease, especially in refractory cases. Several case studies have shown rituximab to be efficacious (Hertl et al 2008;Arin et al 2005). Cyclophosphamide is also used in refractory cases, but it has an unsafe side effect profile (Saha et al 2009).…”
Section: Managementmentioning
confidence: 99%
“…Gebe ve emziren kadınlarda, yetersiz klinik deneyimden dolayı 18 yaş altı hastalarda, aktif hepatit b ve c hastalığı ile HIV pozitif olanlarda ve kontrol edilemeyen infeksiyon ile şiddetli kalp yetmezliği olan hastalarda kullanımı kontrendikedir (25).…”
Section: Protein a İmmünadsorbsiyonu (Pa-unclassified
“…B hücrelerindeki azalmayı takip etmek için son infüzyondan sonra her üç ayda bir kan sayımı yapılması önerilmektedir. Nötrofil sayısı 1.5x 10 9 /l ve/veya trombosit sayısı 75x10 9 /l olan hastalarda ritüksimab tedavisi dikkatli bir şekilde sürdürülmelidir (25). …”
Section: Protein a İmmünadsorbsiyonu (Pa-unclassified